2016
DOI: 10.1177/0194599816633669
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Outcomes of Titanium Ossiculoplasty in Chronic Otitis Media

Abstract: With a minimum follow-up of 2 years, titanium ossiculoplasty provides good long-term hearing results. Modest deterioration in hearing is noted over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
5
32
1
Order By: Relevance
“…This is comparable to similar follow‐up investigations . The patients in this study achieved an ABG of less than 20 dB, which is a common goal for successful hearing improvement …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is comparable to similar follow‐up investigations . The patients in this study achieved an ABG of less than 20 dB, which is a common goal for successful hearing improvement …”
Section: Discussionsupporting
confidence: 87%
“…For ossiculoplasty with a PORP, recently published studies have reported various mean improvements in ABG, including 8.9 dB (standard deviation [SD] 10.3 dB; n = 47), 10 13 dB (SD 13 dB; n = 44), 11 and 14.2 dB (SD 15.3 dB; n = 52). 12 In the present study population, the ABG improved by 8.5 dB (n = 141), which is slightly lower compared to other studies. This improvement is at the lower end of the published ABG scales and may be due to the comparatively small ABG preoperatively (22.5 dB) in our study group.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…PORP results showed a better success and hearing outcome than TORP, which could be explained by poor stability and inadequate coupling at the TORP–footplate interface of the prosthesis, but it was statically insignificant, which is agreed with other studies …”
Section: Discussionsupporting
confidence: 90%
“…Among these materials, none has clearly demonstrated its superiority over the others. According to the literature, closure of the ABG to within 20 dB ranges from 60% to 85% with incus interposition [12][13][14] , from 57% to 84% with hydroxyapatite [11] , and from 60% to 81% with titanium [15][16][17][18] . Most papers comparing hearing outcomes of various ossiculoplasty materials have come to similar conclusions [19][20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%